The systematic literature review process: a simple guide for public health and allied health students - Kabir, Russell; Hayhoe, Richard; Bai, Ancy C. M.; Vinnakota, Divya; Sivasubramanian, Madhini; Afework, Solomon; Chilaka, Marcus; Mohammadnezhad, Masoud; Aremu, Olatunde; Sah, Rajeeb K.; Khan, Hafiz T. A.; Messner, Steph; et al. (International Journal of Research in Medical Sciences, 2023)
A literature review is a key part of all academic research that informs researchers of the existing body of knowledge. Reviews conducted systematically are becoming more appealing to the researcher about two reasons. Firstly, they are robust, strong, comprehensive and reproducible and can appropriately serve the background review of any primary research. Secondly, they are qualified to be a stand-alone piece of academic work that contributes to the scientific body of knowledge. Although researchers and students in higher education who wish to write their dissertations are informed about the need for generating a literature review for primary research, when it comes to conducting a full systematic review, they may have some confusion and doubt on the distinction between a traditional literature review and a systematic review. This paper aims to clarify what a systematic review entails and take the readers’ attention through the practical steps in conducting a systematic review. So, more of a practical step-by-step guide, rather than theoretical discussion of content, has been included. This paper would benefit early-career researchers, undergraduate students and many post-graduate students who wish to write their papers or dissertations based on a systematic review.